Impact of post-chemoradiotherapy superselective/selective neck dissection on patient reported quality of life. (July 2016) - Wang, Kyle; Amdur, Robert J.; Mendenhall, William M.; Green, Rebecca; Aumer, Shannon; Hackman, Trevor G.; Zanation, Adam M.; Zevallos, Jose P.; Patel, Samip N.; Weissler, Mark C.; Chera, Bhishamjit S.
Highlights: Neck dissection (ND) extent varies after CRT for head and neck cancer. We report QoL in pts who had superselective/selective ND after deintensified CRT. We saw acute but not long-term decrease in ND Impairment Index (functional) score. Limited post-CRT ND did not prevent recovery of most QoL metrics back to baseline. These data complement efficacy data for use of limited post-CRT NDs when indicated. Summary: Objectives: To describe patient-reported quality of life (QoL) for patients with HPV/p16-positive oropharyngeal squamous cell carcinoma undergoing post-chemoradiation (CRT) superselective or selective neck dissection (ND) as part of a prospective de-intensification study. Materials and methods: Patients received 60 Gy IMRT with concurrent weekly cisplatin (30 mg/m 2 ), followed by preplanned neck dissection of only originally involved nodal levels. QoL measures were assessed using the EORTC QLQ-C30 (general), EORTC H&N-35 (head and neck specific), EAT-10 (swallowing), and NDII (Neck Dissection Impairment Index) questionnaires. Early and late post-ND time points were compared to baseline and post-CRT/pre-ND time points. Results: 37 patients underwent post-CRT superselective or selective ND. Median # of levels and nodes dissected were 2 and 12, respectively. EORTC QLQ-C30, H&N-35, and EAT-10 QoL scores worsened after CRT but continued to improve thereafter despite post-CRT ND. NDII score worsened initially after ND at the early post-ND time point ( p  = 0.023) but had recovered by the late post-ND time point ( p  = 0.672). Initial decrease in NDII was greater with ⩾12 nodes dissected ( p  = 0.007) and was correlated with the total number of nodes dissected (Spearman p  = 0.027). Conclusion: Use of post-CRT superselective and selective ND did not prevent recovery of most QoL metrics to near baseline. There was early but not late decrement in neck dissection specific QoL (NDII), more pronounced with more nodes dissected.